Characterization and comparison of lipids in bovine colostrum and mature milk based on UHPLC-QTOF-MS lipidomics. (October 2020) - Li, Mohan; Li, Qilong; Kang, Shimo; Cao, Xueyan; Zheng, Yan; Wu, Junrui; Wu, Rina; Shao, Junhua; Yang, Mei; Yue, Xiqing
Graphical abstract: Highlights: We analyzed lipids in bovine colostrum (BC) and mature milk (BM). Thirteen subclasses of 335 lipids were identified in BC and BM. Sixty-three significantly different lipids (SDLs) were identified between BC and BM. We investigated the correlations and related metabolism pathways of these SDLs. Our results provided insight into alterations in bovine milk lipids during lactation. Abstract: Lipids in bovine milk have several biological activities, with implications for human health and the physical functionality of foods. However, alterations in the lipid profile of bovine milk during lactation are not well-studied. This study aimed to identify differences in lipids between bovine colostrum and mature milk, using a lipidomics approach. Using an advanced mass spectrometry-based quantitative lipidomics approach, 335 lipids assigned to 13 subclasses were characterized in bovine colostrum (BC) and mature milk (BM). In total, 63 significantly differential lipids (SDLs) were identified. Among the 63 SDLs, the levels of 21 lipids were significantly lower in BM than in BC, including 5 glycerophosphatidylethanolamines (PEs), 1 glycerophosphatidylglycerol (PG), and 15 triacylglycerols (TGs). The levels of the remaining 42 lipids increased in BM, including 1 cardiolipin (CL), 9 diacylglycerols (DGs), 9 dihexosylceramides (Hex2Cers), 3 hexosylceramides (HexCers), 3 glycerophosphatidic acids (PAs), 2 glycerophosphatidylcholines (PCs), 12 PEs, and 3 TGs. Furthermore, the correlations and related metabolic pathways of these 63 SDLs were analyzed to explore the mechanisms that alter bovine milk lipids during lactation. The seven most relevant pathways identified herein, ranked in accordance with their degree of influence on lactation, were glycerophospholipid metabolism, sphingolipid metabolism, glycerolipid metabolism, glycosylphosphatidylinositol-anchor biosynthesis, linoleic acid metabolism, alpha-linolenic acid metabolism, and arachidonic acid metabolism. Our results provide essential insights into mechanisms underlying alterations in bovine milk lipids during different lactation periods, along with practical information of specific nutrition and quality assessments for the dairy industry.